2004
DOI: 10.1128/mcb.24.24.10636-10649.2004
|View full text |Cite
|
Sign up to set email alerts
|

The CRM1 Nuclear Export Receptor Controls Pathological Cardiac Gene Expression

Abstract: Diverse pathological insults trigger a cardiac remodeling process during which myocytes undergo hypertrophy, with consequent decline in cardiac function and eventual heart failure. Multiple transcriptional regulators of pathological cardiac hypertrophy are controlled at the level of subcellular distribution. For example, prohypertrophic transcription factors belonging to the nuclear factor of activated T cells (NFAT) and GATA families are subject to CRM1-dependent nuclear export but are rapidly relocalized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 72 publications
1
68
0
1
Order By: Relevance
“…Because strong toxic side effects have been encountered with LMB during clinical trials for cancer, many efforts have focused on novel CRM1 antagonists; and some agents, such as PKF050-638 or 5219668, recently have been identified. 10 The results of the current study demonstrated that CRM1 expression is associated with advanced ovarian carcinomas that have an aggressive behavior. Thus, CRM1 expression is related to poor patient outcome.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Because strong toxic side effects have been encountered with LMB during clinical trials for cancer, many efforts have focused on novel CRM1 antagonists; and some agents, such as PKF050-638 or 5219668, recently have been identified. 10 The results of the current study demonstrated that CRM1 expression is associated with advanced ovarian carcinomas that have an aggressive behavior. Thus, CRM1 expression is related to poor patient outcome.…”
Section: Discussionmentioning
confidence: 67%
“…This transporter has a comparably broad substrate range and mediates the export of leucine-rich NES-bearing proteins and the transfer of messenger RNAs (mRNAs). [4][5][6][7][8] Mechanistic studies have demonstrated an increasing number of NEScontaining signaling molecules that depend on the CRM1 nuclear export pathway, p53, 9 histone deacetylase 5 (HDAC5), 10 protein kinase 1 (Akt1), 11 epidermal growth factor receptor (EGFR), 12 and others. 13,14 Therefore, this shuttling process controls several elements of pathways that have been identified as important in tumor biology.…”
mentioning
confidence: 99%
“…The nuclear export of class IIa HDACs is inhibited by leptomycin B, which suggests that the export receptor CRM1 may interact with the leucine-rich NES found in class IIa HDACs Harrison et al, 2004). Whereas no CRM1 class IIa HDACs association has ever been formally documented, overexpression of CRM1 promotes cytoplasmic accumulation of HDAC7 .…”
Section: Subcellular Distributionmentioning
confidence: 99%
“…Instead, these HDACs are shuttled from the nucleus to the cytoplasm in response to stress (Figure 3), which provides a posttranslational mechanism to override HDACmediated repression of cardiac growth (27,28,31). This redistribution of HDACs frees MEF2 (and other transcription factors) to associate with HATs (32,33), resulting in increased local histone acetylation and activation of downstream genes that promote cell growth.…”
Section: Posttranslational Regulation Of Class II Hdacsmentioning
confidence: 99%